Market Metamorphosis: Decoding The Marketing Mix Landscape in The Traditional Market of Cisalak, Depok, Indonesia, Amid The E-Commerce Epoch - WB Raharjo, Ari; Elida, Tety (Universitas Mercu Buana, 2024)
The rapid development of e-commerce and the Covid-19 pandemic have led consumers to adopt new shopping habits from home. This situation initially resulted in the closure of offline stores and traditional markets. Currently, some offline stores have begun to reopen, and traditional markets have played a role in the local economy. Amid the current rapid development of e-commerce and the changing consumer behavior, the phenomenon of traditional markets that continue to thrive is intriguing to investigate. The aim of this research is to understand the perceptions of consumers in Cisalak Market, Depok, and e-commerce regarding products, prices, promotions, and locations. This study employs descriptive methods and validity, reliability, and Mann-Whitney tests with 100 respondents from Cisalak Market consumers in Depok. A questionnaire is used to collect data on variables such as products, prices, promotions, and locations in traditional markets and e-commerce. The results show that customer perceptions of products in traditional markets differ from those in e-commerce. Meanwhile, perceptions of prices, promotions, and locations do not significantly differ between traditional markets and e-commerce.